Health Care Providers Acceptance and Knowledge about Traditional Health Services at Community Health Centers in Pekalongan, Central Java, Indonesia - Sri Mumpuni Yuniarsih; Joyo Wasito; Moh. Khotibul Umam (Universitas Respati Yogyakarta, 2023)
Traditional health services are public health services and are a system of treatment/care that is based on the philosophy and basic concepts of the whole person so that clients will be seen in a more humane way. Traditional health services are carried out using skilled methods, ingredients, or both. On average, health workers do not know about traditional health services at the Puskesmas and have never applied traditional health services, either in therapy or herbal ingredients, due to a lack of knowledge about traditional health. With increased knowledge and acceptance of traditional health services, it is hoped that this will become a promotive and preventive effort to maintain health independently. This research contributed to describing the knowledge and acceptance of health workers towards traditional health services at community health centers in Pekalongan Regency. This type of research is descriptive and quantitative with a cross-sectional design. Data collection is based on primary data in the form of a questionnaire. Data analysis using univariate analysis. A sample of 92 respondents with the Cluster Random Sampling technique. The research results were analyzed using univariate analysis. The results showed that the majority of respondents in the good knowledge category were women 60.9%, the good knowledge of the majority of respondents with an age range of 31-40 years was 31.5%, the good knowledge of the majority of D3 education levels was 48.9%, the good knowledge category was the majority of the nursing profession by 30 .4%. The majority of respondents in the good acceptance category were women, 39.1%, and the good acceptance of the majority of respondents in the age range of 41-50 years was 23.9%. The good acceptance of the majority of D3 education levels was 37%, and the good acceptance of the majority of the profession of nurses and midwives was 20.7%. Knowledge of the majority of health workers in the good category was 79.3%, and the acceptance of health workers was in the good category at 54.3%.